2002
DOI: 10.1053/jlts.2002.35664
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma: Can it be considered a controversial indication for liver transplantation in centers with high rates of hepatitis C?

Abstract: Hepatocellular carcinoma (HCC) is still considered a controversial indication for liver transplantation (LT), mainly because of long waiting times and underlying viral cirrhosis. The goal was to evaluate the outcome of LT in 104 patients with HCC and cirrhosis, mainly hepatitis C virus (HCV)-related, in a center with a short waiting time (median, 105 days). Four groups were formed according to the HCC and HCV status: HCV positive with HCC (group 1, n ‫؍‬ 81), HCV negative with HCC (group 2, n ‫؍‬ 23), HCV posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 16 publications
10
39
1
Order By: Relevance
“…10,35 Indeed, several studies have shown that the differentiation degree and microvascular invasion represent direct indicators of the biologic progression of HCC, being associated with tumor recurrence and poor long-term survival. 4,6,8,10,13,35,36 In 1 study that evaluated the results of OLT in 48 patients in which the pre-OLT pathologic examination showed only moderately or well differentiated tumors, the 5-year survival rate reached 75%, regardless of the number or size of the lesions. 10 Unfortunately, there are data suggesting that this strategy might not be adequate because the tumor degree based on the pre-OLT assessment is potentially misleading, without a direct correlation with final histopathologic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,35 Indeed, several studies have shown that the differentiation degree and microvascular invasion represent direct indicators of the biologic progression of HCC, being associated with tumor recurrence and poor long-term survival. 4,6,8,10,13,35,36 In 1 study that evaluated the results of OLT in 48 patients in which the pre-OLT pathologic examination showed only moderately or well differentiated tumors, the 5-year survival rate reached 75%, regardless of the number or size of the lesions. 10 Unfortunately, there are data suggesting that this strategy might not be adequate because the tumor degree based on the pre-OLT assessment is potentially misleading, without a direct correlation with final histopathologic features.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of cirrhosis was HCV in 188 cases (associated with alcohol abuse in 30), HBV in 17 cases, alcohol in 45 cases, and other causes in 7 cases. The median body mass index was 26 kg/m 2 (range, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. According to the Child-Pugh-Turcotte classification, 118 patients corresponded to group A, 93 corresponded to group B, and 46 corresponded to group C. Two hundred thirty-one patients had tumors within the MC and 26 had tumors beyond the MC on the basis of radiology.…”
Section: Patients' Baseline Featuresmentioning
confidence: 99%
“…18 On the other hand, the original indication may have an effect, sometimes long-term, on psychological status, particularly if there is a risk of recidivism of the illness as HCV hepatitis 17 or hepatocellular carcinoma. 19 Other characteristics such as alcohol abuse or tobacco addiction, or a socioprofessional situation may also influence the QOL. Gender may also be important; in this study, 73% of subjects were male.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that both tumor-and HCVrelated recurrent diseases hamper the outcome of these patients. 30 …”
Section: Other Host Variablesmentioning
confidence: 99%